2021
DOI: 10.1007/s00264-021-05077-3
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and rate of return to play in elite athletes following arthroscopic surgery of the hip

Abstract: Background The tremendous physical demands of elite performance increase the risk of elite athletes sustaining various orthopaedic injuries. Hip pain is common in high-level athletes representing up to 6% of all athletic injuries. Expedient diagnosis and effective treatment are paramount for their future sporting careers and to prevent subsequent joint degeneration. Purpose This systematic review aimed to evaluate the outcome and the rate of return to play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…In addition, by 6 months, the UCLA activity scores indicated that they were just as active as the controls, as the 8/10 average score indicates "regularly participating in very active sports." Our HOS SS improved by 88% up to 82.6, and similar ranges have been reported in runners 2-5 years postoperatively (5,15) and elite athletes 2-3 years postoperatively (8). In these regards, it can be assumed that the patients in our study found a similar level of relief and recovery compared with individuals of similar age and dysfunction as reported in a recent large-scale FAIS meta-analysis (8).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, by 6 months, the UCLA activity scores indicated that they were just as active as the controls, as the 8/10 average score indicates "regularly participating in very active sports." Our HOS SS improved by 88% up to 82.6, and similar ranges have been reported in runners 2-5 years postoperatively (5,15) and elite athletes 2-3 years postoperatively (8). In these regards, it can be assumed that the patients in our study found a similar level of relief and recovery compared with individuals of similar age and dysfunction as reported in a recent large-scale FAIS meta-analysis (8).…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have observed that footballers develop knee and hip osteoarthritis later on in their active playing years and early on after retirement. Most would require surgical intervention at some stage [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Most of these studies diagnose OA based on radiological criteria (e.g., the Kellgren–Lawrence criteria) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…If one considers the hip joint and PTOA, arthroscopic hip procedures usually lead to short- and medium-term symptom improvement. However, there is inconclusive data on the long-term outcomes after these procedures [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…9 Return to sport after hip arthroscopy in professional athletes is quite high, with 61-91% of professional football players, [12][13][14][15][16][17] 82-95% of professional baseball players, [12][13][14]17,18 81-87% of professional basketball players, and 90-96% of professional hockey players returned to sports at a professional level. [12][13][14]17 Similarly, NCAA Division one athletes return to sports at the same, or higher, nearly 90% of the time after hip arthroscopy. 19 One may consider why high-level athletes return at such higher levels than lower-level competitive athletes.…”
mentioning
confidence: 99%